Sistem Informasi Pelayanan Barberhome Berbasis Website (Studi Kasus : Barbershop D’Goenting) - Salahudin Robo; Muh Riandi Widiyantoro; Adi Putra Mika Surya Negara; Trisno (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
The modern-day technique of Barbershop D'Goenting's provider, clients nevertheless must go to the closest Barbershop without delay to get shaving offerings. Meanwhile, the hassle confronted via way of means of Barbershop D'Goenting is that it has now no longer supplied hair care offerings to clients' homes. Therefore, so as for Barbershop D'Goenting to enhance provider quality, it have to innovate. The innovation supplied via way of means of the researcher is to layout a website-primarily based totally barberhome provider statistics machine. In this observe, the fishbone evaluation approach is used to gain in-intensity purpose and impact problems, the UML layout approach is locate case diagrams, interest diagrams, series diagrams, and sophistication diagrams, in addition to the waterfall version improvement approach. The consequences of this observe layout a web-primarily based totally barberhome provider machine, specifically a call-to-domestic hair provider machine wherein clients can area orders, pick, and pick the capster as desired. The cause of this machine is designed to enhance D'Goenting's barbershop offerings in order that clients can get haircut offerings from domestic while not having to return back without delay to the barbershop